Spot weather forecast : a fire liturgy - Goodan, Kevin, 1969- (Alice James Books, 2021)
"From the unique perspective of a U.S. Forest Service elite, a Type 1 Interagency "Hotshot" Crew (the "SEAL Team Six of the firefighting world"), poems weave together memory, urgency, and the passage of time. Features segments from actual incident reports, forcing readers to witness what it's like to stand before an inferno, walking with one foot in the black. An elegy for the self and the damage one sustains fighting wildfires"--